Psychoneuroendocrine associations with momentary pelvic pain in endometriosis [data] - Stein, Katharina van; Stoffel, Martin; Eckstein, Monika; Ditzen, Beate (Universität, 2025)
Abstract: Endometriosis is a gynecological condition which often causes chronic or recurrent pelvic pain (CPP). The disease can thereby impose a significant burden on affected individuals and their romantic relationships. Existing research highlights the substantial influence of stress, social support, and hormonal factors on pain experience, but data from daily life is scarce. This ecological momentary assessment (EMA) study aimed to explore the association of stress, partners’ social support styles, cortisol, and oxytocin in daily life with pain experiences among women with CPP (N = 66) across 7 days, resulting in a dataset with up to 2100 data points per variable across multiple measures. Stress was positively correlated with pain ratings both within and between individuals, while no significant associations were observed between salivary cortisol or oxytocin levels and pain ratings. Distracting as well as solicitous social support was positively related to higher pain ratings on a between-person level but showed no or slightly negative associations with pain on a within-person level. These findings suggest that both stress and social support can adversely impact pain experience in endometriosis. This knowledge is essential for developing comprehensive interventions: While stress management can be beneficial, the role of social support is more intricate, requiring tailored guidance for close others and their support behavior.
Gefördert durch: Deutsche Forschungsgemeinschaft: SFB1158
Gesehen am 12.01.2026
Keywords: Forschungsdaten; Datenbank